PENERAPAN RESTORATIVE JUSTICE TERHADAP PEMBELI HANDPHONE HASIL CURIAN BERDASARKAN PERJA REPUBLIK INDONESIA NOMOR 15 TAHUN 2020 - Putri, Erya Intan Virnanda; Aven, Ghina Salsabila (Legacy: Jurnal Hukum dan Perundang-Undangan, 2025)
The growing trade of second hand smartphones through digital platforms has inadvertently enabled the circulation of stolen goods, particularly from theft. Many buyers unknowingly purchase these items and risk prosecution under Article 480 of the Indonesian Criminal Code on fencing. This creates a legal imbalance, especially in proving the element of intent (mens rea) in buyers acting in good faith. This study examines the effectiveness of applying restorative justice to buyers of stolen phones who lack criminal intent, based on Indonesian Prosecutorial Regulation No. 15 of 2020. Using a normative legal approach, the research analyzes laws, legal theories, and restorative justice principles. Findings indicate that restorative justice can offer a more humane and fair alternative to conventional prosecution, provided certain conditions are met such as the absence of a criminal record, a peaceful agreement between parties, and restitution to the victim. However, its practical application remains limited due to structural challenges and a lack of awareness among law enforcement and the public. Therefore, a more inclusive legal policy is needed to extend restorative justice to third parties who are not directly involved in crimes but are legally affected under the current system.